Effect of dietary coarsely ground corn on broiler live performance, gastrointestinal tract development, apparent ileal digestibility of energy and nitrogen, and digesta particle size distribution and retention time. (7th January 2015) - Xu, Y.; Stark, C. R.; Ferket, P. R.; Williams, C. M.; Pacheco, W. J.; Brake, J.
Abstract : Dietary structural material has been reported to improve broiler live performance and gastrointestinal tract (GIT) function. In this 50 d cage study, the effects of coarsely ground corn (CC) inclusion on broiler live performance, GIT development, apparent ileal digestibility (AID) of energy and nitrogen (N), and digesta particle size distribution and retention time were investigated. This study included 3 CC inclusions (0, 25, and 50% fine corn [FC] replaced by CC), with 6 replicate cages of 10 birds per treatment. The feed conversion ratio (FCR) at 35 and 42 d was improved ( P < 0.01) as the dietary inclusion of CC increased without effect on feed intake. The 50% CC diet increased absolute and relative gizzard weight at 42 d of age as compared to diets with 0 and 25% CC ( P < 0.01). Dietary CC increased absolute proventriculus weight at 28 d of age ( P < 0.05). A numerically lower gizzard digesta pH ( P < 0.08) was observed at 28 d but not 42 d of age, and there was no difference in proventriculus, jejunum, or ileum digesta pH at 28 or 42 d of age. The 25 and 50% CC treatments increased the digesta retention time at 30 and 45 d of age ( P < 0.05 and P < 0.01, respectively). The 25 and 50% CC treatments improved AID of energy by 7.1 and 8.2%, respectively, when compared with the 0% CC treatment, and they improved AID of N by 12.2 and 12.4%, respectively ( P < 0.01). The digesta particles in the jejunum exhibited a similar distribution, with a dgw (geometric mean diameter by mass) of 218, 204, and 181 μm when 0, 25, of 50% CC diets were consumed, respectively. In conclusion, birds fed pelleted and screened diets that contained 25 and 50% CC exhibited increased BW, improved FCR, and increased AID of energy and N, which was probably due to enhanced gizzard development and greater digesta retention time.